Cost of cancer care for patients undergoing chemotherapy: The Elements of Cancer Care study. Issue 2 (13th April 2015) - Ward, Robyn L; Laaksonen, Maarit A; van Gool, Kees; Pearson, Sallie‐Anne; Daniels, Ben; Bastick, Patricia; Norman, Richard; Hou, Changhao; Haywood, Philip; Haas, Marion
Abstract Aim To determine the monthly treatment costs for each element of cancer care in patients receiving chemotherapy and to apportion the burden of cost by financing agent (Commonwealth, State government, private health insurer, patient). Methods A cohort of 478 patients (54% breast, 33% colorectal and 13% non‐small‐cell lung cancer) were recruited from 12 centers representing metropolitan and regional settings in public and private sectors. Primary data were linked to secondary data held in New South Wales state (Admitted Patients and Emergency Department Data) and Commonwealth (Medicare and Pharmaceutical Benefits) databases. The monthly treatment costs of each element of care and the funding agent were calculated from secondary health data. Results Across all tumor types, the mean monthly treatment cost was 4162 (10%–90% quantiles 1018–8098; range 2853 [adjuvant colorectal] to 5622 [metastatic lung]), with 54% of this cost borne by Commonwealth government, 26% by private health insurers, 14% by State government and 6% by patients. The mean monthly costs of treating metastatic disease were 1415 greater than those for adjuvant therapy. The mean monthly costs were contributed to by inpatient care (1657, 40%), chemotherapy prescriptions (1502, 36%), outpatient care (452, 11%) and administration of chemotherapy (364, 9%). Conclusion All four funders have a shared incentive to reduce absolute monthly treatment costs since their proportional contribution is relatively constant for most tumor types and stages. There are opportunities to reduce cancer care costs by minimizing the risk of inpatient hospital admissions that arise from chemotherapy administration and by recognizing incentives for cost‐shifting.